The Influence of Peer Support on Student Well-Being: Insights from the PISA 2018 Study - Zhang, Mingxiu; Zhang, Yu; Ma, Yishan; Shang, Yuandong (Journal of Advanced Research in Education, 2025)
This study, based on data from PISA 2018, investigates the mechanism through which peer support influences student well-being, specifically examining the mediating role of resilience and the moderating role of perceived family support in this relationship. The research sample comprised approximately 10,000 15-year-old students from four provinces/municipalities in China (Beijing, Shanghai, Jiangsu, Zhejiang). The results indicated that peer support significantly and positively predicted student well-being, and resilience played a partial mediating role in this relationship. Furthermore, perceived family support significantly moderated the effects of peer support on resilience and of resilience on student well-being. Specifically, the influences of peer support on resilience and of resilience on well-being were more pronounced among students with high levels of perceived family support. This study extends social support theory, validates the proposed mediation and moderation models, and provides concrete references for educational practice. It emphasizes the importance of fostering both peer support and perceived family support in educational settings to enhance student resilience and well-being.